Research progress in the treatment of severe aplastic anemia - FU Chen, LI Ping (Jichu yixue yu linchuang, 2024)
Severe aplastic anemia(SAA)is a critically ill disease of the blood system that progresses rapidly, has a high mortality rate, and a very poor prognosis. The application of drugs like androgens and Eltrombopag has significantly increased the survival rate of those with aplastic anemia (AA), compared with horse antithymocyte globulin(H-ATG) and cyclosporine, which was once the standard treatment. Patients who do not respond well to immunotherapy or experience a recurrence of symptoms post-treatment have the option to undergo hematopoietic stem cell transplantation (HSCT). The advancement of pre-treatment techniques for HSCT and the utilization of diverse medications following the transplantation procedure have contributed to reduced incidence of graft versus-host disease (GVHD) and improved transplant success. Allogeneic hematopoietic stem cell transplantation has become a hot topic in clinical research. This study summarizes the transplant and non transplant treatments of SAA in recent years, and analyzes its efficacy and related advantages and disadvantages.